Treatment of tuberculous aortic pseudoaneurysm associated with vertebral tuberculosis: A case series and a literature review. Issue 15 (April 2018) - Xue, Jing; Yao, Yimin; Liu, Limin
Abstract: Rationale: Tuberculous aortic pseudoaneurysm associated with vertebral tuberculosis is a rare disease but with very high mortality. We review the literature and find 19 reports with 22 patients. Here we report three cases with vertebral tuberculosis, who also have tuberculous pseudoaneurysm of the aorta. These patients were treated by different methods. We try to analyze the epidemiology, pathogenesis, presentation, and management of this disease to find the best treatment. Patient concerns: The patients presented with different symptoms such as pain (chest, abdominal or back), fever, blood volume reduction or hemorrhagic shock symptoms. Large mass also could be observed by imaging. In addition to clinical manifestations, enhanced computed tomography or magnetic resonance imaging could also help the diagnosis of this disease. Diagnoses: Tuberculous aortic pseudoaneurysm associated with vertebral tuberculosis. Interventions: Three patients were treated with anti-tuberculosis(TB) drugs or combined with different sequences surgical treatment: Case 1 refused to receive pseudoaneurysm surgery and only had anti-TB drug treatment; Case 2 received thoracic spinal surgery first; Case 3 received endovascular stent grafting. Outcomes: Two patients (case 1 and case 2) who refused to undergo aneurysm surgery died. The last patient (case 3) underwent endovascular repair and antibiotic therapy for tuberculosis, and the postoperative course was uneventful; the patient recovered and survived. Lessons: Once the diagnosis of tuberculous pseudoaneurysm is confirmed, surgical treatment should be provided immediately combined with anti-tuberculosis drugs. The aim of the treatment is to save lives, prevent relapse, and facilitate the return to normal life, regardless of the size of the pseudoaneurysm. The pseudoaneurysm should be treated first to prevent aneurysm rupture before the vertebral tuberculosis surgery.